"Lugares de palavra": as aulas de Ciências descritas por professores de 3° e 4° ano do Ciclo I do Ensino Fundamental e as marcas da tradição oral na escola - Calil, Angela de Almeida Mogadouro (2005)
This work aims at investigating didatic practices, contents, resources and the use of didatic support materials in Natural Science classes described by teachers of 3rd and 4th grades and the interference of such teacher s education profile, of the Science content setting in the school curriculum and of school culture on this process. This empirical research has been accomplished with qualitative and analitic-descriptive methodology of such practices showed in interviews (with the aid of a program built and tested for this specific end) structured by 10 teachers of this level of schooling from municipal public schools in the city of São Paulo, all participants in a development program to the teaching of Natural Science. The research has also included the analysis of legal school documents relative to this curricular subject in the first years of Primary School. The results obtained allowed the description of the profile of the teachers who were interviewed: the great majority were graduated young women from low-income and low-education families, living in the same region as their students. Furthermore, by their practices it was possible to recognize the Science classes at the end of Primary School as a place of words , namely, the results permitted the identification of orality culture marks, according to M. Certeau s definition, in the school internal relationships (pedagogic coordinator, teachers, students), as well as the existence of a readers comunity in the school, in the perspective of Roger Chartier, specially related to oral texts about the national curricular patterns (Parâmetros Curriculares Nacionais) and their guidance concerning the Science teaching in the Primary School.